2005
DOI: 10.1128/jb.187.2.576-592.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Staphylococcus aureus Musculoskeletal Isolates

Abstract: Much of the research aimed at defining the pathogenesis of Staphylococcus aureus has been done with a limited number of strains, most notably the 8325-4 derivative RN6390. Several lines of evidence indicate that this strain is unique by comparison to clinical isolates of S. aureus. Based on this, we have focused our efforts on two clinical isolates (UAMS-1 and UAMS-601), both of which are hypervirulent in our animal models of musculoskeletal infection. In this study, we used comparative genomic hybridization t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 70 publications
2
79
0
Order By: Relevance
“…S. aureus strain UAMS-1 is a well-characterized, highly virulent clinical isolate, and its genetic composition has recently been determined (7,8,10,11,16). The mRNA half-lives of all transcripts produced during log-phase UAMS-1 and isogenic sarA mutant cell growth were measured using S. aureus Affymetrix GeneChips (Saur2a).…”
Section: Resultsmentioning
confidence: 99%
“…S. aureus strain UAMS-1 is a well-characterized, highly virulent clinical isolate, and its genetic composition has recently been determined (7,8,10,11,16). The mRNA half-lives of all transcripts produced during log-phase UAMS-1 and isogenic sarA mutant cell growth were measured using S. aureus Affymetrix GeneChips (Saur2a).…”
Section: Resultsmentioning
confidence: 99%
“…There is not enough space here to highlight all the comparative genomics analyses of S. aureus performed to date (22,(73)(74)(75). However, the study by Fitzgerald et al was the first to use a comparative microarray approach to study the evolution of MRSA (76).…”
Section: Sccmec Typingmentioning
confidence: 99%
“…However, these studies did not use a collection of isolates from specific invasive diseases and therefore do not rule out the possibility that specific lineages or genes are associated with specific types of infection, such as osteomyelitis or septic arthritis. To date, the only genome comparison study relevant to S. aureus bone infections has been done using comparative genome microarray hybridisations of the S. aureus UAMS-1 strain, isolated from an osteomyelitis patient, with a range of genome sequenced strains [41]. These authors found variations in the complement of adhesin, toxin, exoenzyme and regulatory genes.…”
Section: Genomic Features Of Staphylococci Associated With Bone Infecmentioning
confidence: 99%